A New Lignan from the Fruit of Schisandra lancifolia and Its Anti-HIV Activity - Li , Yin-Ke; Ma, Yin-Hai; Peng, Yong-Fang; Dai, Yun; Li, Gan-Peng (Asian Journal of Chemistry, 2010)
Phytochemical investigation of the fruit of Schisandra lancifolia led to the isolation and identification of a new lignan named Schlanctins A. The structures was elucidated by analysis of spectroscopic data and it activity against HIV-1 was evaluated. It showed anti-HIV activity with an EC50 value of 1.82 μM.